Intranasal Splint in Nasal Septal Surgery: Is It Necessary? (Medicine Today, 2020)
Introduction: After SMR/septoplasty with or without turbinate surgery, it needs to keep apart the septum and turbinates upto their complete healing otherwise there is a chance of adhesion (synechia) formation. To prevent this there are variousprocedures. To place an intranasal splint in one or both sides of the septum is one of them. Nowadays there raised thequestion of whether the splinting is necessary or not. There is no significant difference in result with or without anintranasal splint. Weighing against the co-morbidities the routine use of an intranasal splint can no longer be justified.Materials and Methods: This is a randomized control study of 200 patients of SMR/septoplasty, done for nasal septaldeviation causing symptoms in Cumilla Medical College Hospital in the period of January 2016 to December 2019. Theywere equally divided into two groups, group-A were operated placing an intranasal splint and group-B with no intranasalsplint. They were followed up for 6 weeks to detect any synechia and co-morbidities.Result: The age of our patients wasranged from 13-49 years with a mean age of 22.45 years. The male to female ratio is 1.78:1. Synechia was found in 4% ofthe splinted group and 6 of the nonsplinted groups. Co-morbidities were detected more in the splinted group than that ofnon-splinted. In INS group these were found as follows: pain in the nose, face and head (26%), faint during removal ofnasal splint (6%), nasal obstruction (38%), the anxiety of splint removal in the postoperative period (35%) and vestibulitisdue to persistent irritation by a splint (17%).Conclusion: There is little significant advantage of using intranasal splintroutinely in septal surgery to prevent synechia formation.Medicine Today 2020 Vol.32(2): 126-129